![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x(x+5) - (3x+18) (x-1) + 8 = 20
3x.x + 3x.5 - ( 3x.x-3x.1+18.x-18.1)+8=20
3x2 + 15x - ( 3x2 - 3x + 18x - 18 ) + 8 = 20
3x2 + 15x - 3x2 + 3x - 18x + 18 + 8 = 20
3x2 - 3x2 + 15x + 3x - 18x + 26 = 20
26 = 20 ( vô lý )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có :
\(8x\left(3x-8\right)+6x\left(-4x+7\right)=-88\)
\(\Leftrightarrow24x^2-64x-24x^2+42x=-88\Leftrightarrow-22x=-88\Leftrightarrow x=4\)
`8x (3x-8) +6x (-4x+7)=-88`
`-> 24x^2 - 64x - 24x^2 + 42x=-88`
`-> (24x^2 - 24x^2)+(-64x+42x)=-88`
`-> -22x=-88`
`->x=-88 : (-22)`
`->x=4`
Vậy `x=4`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-3\right)\left(x^2+3x+9\right)+x\left(x+2\right)\left(2-x\right)=1\)
\(x^3-3^3+x\left(2^2-x^2\right)=1\)
\(x^3-27+4x-x^3=1\)
\(4x-27=1\)
\(4x=28\)
\(x=7\)
Vậy x = 7
20 - 3x = 8
3x = 20 - 8
3x = 12
x = 12 : 3
x = 4
*** cho mik nha !!!
20-3x=8
3x=20-8
3x=12
x=12:3
x=4